Intensive care clinicians’ experiences of palliative withdrawal of mechanical ventilation: a qualitative study - Nikolaos Efstathiou; Brandi Vanderspank-Wright; Fotini Kristina Michaela Diridis; Michelle Orr; Marianne Baernholdt (BMJ Open)
Objectives To explore intensive care unit (ICU) clinicians’ experiences of withdrawing mechanical ventilation during end-of-life care.Design An exploratory qualitative design was used, with data collected via semistructured, face-to-face online interviews and analysed using reflexive thematic analysis.Participants We recruited ICU clinicians from two hospitals within the West Midlands region of the UK.Data collection Semistructured, face-to-face online interviews were used to explore experiences with limitation of life-sustaining treatments in ICU, decision-making and practices for withdrawing mechanical ventilation.Findings 22 ICU clinicians were interviewed (Physiotherapist=1, Advanced Critical Care Practitioners=4, Physicians=9 and Nurses=8), of which 13 were women (59%). Four themes were developed. (1) Multilayered communication: effective communication was key in planning withdrawal and informing family members, with conflicts arising from cultural differences. (2) Considerations regarding the mode of withdrawing invasive mechanical ventilation: clinicians expressed differing preferences for the method of mechanical ventilation withdrawal. (3) Multiprofessional teamwork: collaborative teamwork was vital, with palliative care practitioners consulted during conflicts or challenging symptoms. (4) Clinicians’ feelings and impact: clinicians empathised with families and experienced psychological burden.Conclusions Physician preferences influence the withdrawal process, which is communicated within the multidisciplinary team. Clear protocols can help reduce ambiguity and support less experienced clinicians. Reflection on these practices may help mitigate burnout and compassion fatigue. Further research should examine the effects of physician demographics and patient cultural diversity on the withdrawal process.